Assessing Senior High School Students’ Critical Thinking Skills on Global Warming in Samarinda - Muliati Syam; Shelly Efwinda; Dinda Ar-Rizalah Pujie Rahmayana Putri; Habibah Habibah; Abdul Hakim; Puardmi Damayanti (JPPPF: Jurnal Penelitian & Pengembangan Pendidikan Fisika)
Global warming is a problem that has received attention from various countries because it can cause climate change accompanied by extreme natural disasters and threats to human health and survival on Earth. The problems of global warming will continue if not critically considered by the next generation. This study aimed to explore the level of critical thinking skills of high school students in Samarinda City and whether there are significant differences between the essential skills of thinking of public and private high school students and between male and female students. This research was an exploratory study using the survey method. The population in this study was all grade X high school students in Samarinda City, and a sample of 5 schools with details of 3 public and two private high schools totaled 274 students. The results showed that students' critical thinking skills were in the less crucial category, with the highest score on the likelihood and uncertainty analysis indicator of 63.89 and the lowest score on the problem-solving and decision-making indicator of 40.21. Public high school students demonstrated significantly higher critical thinking skills than their private school peers, while no significant difference was found between male and female students. The results of this study can be used as a reference for stakeholders to find out which indicators of critical thinking skills still need to be developed and take practical actions for the development of climate change education, especially in Samarinda. These findings highlight the need for targeted interventions to improve critical thinking skills in climate change education among high school students, particularly in Samarinda.